Characterization of the complete chloroplast genome of Sophora tonkinensis Gagnep. - Wenlong Zhang; Liping Liu; Jianke Wang; Li Li; Guohong Li (Mitochondrial DNA. Part B. Resources, 2019)
In this study, the complete chloroplast (cp) genome of Sophora tonkinensis Gagnep. was determined through Illumina sequencing method. The complete chloroplast genome of S. tonkinensis was 155,640 bp in length and contained a pair of IR regions (25,925 bp) separated by a small single copy region (18,205 bp) and a large single copy region (85,585 bp). The cp genome of S. tonkinensis encoded 127 genes including 84 protein-coding genes, 35 tRNA genes, and 8 ribosomal RNA genes. The overall GC content of S. tonkinensis cp genome is 36.4%. By phylogenetic analysis using the maximum-likelihood (ML) method, S. tonkinensis showed the closest relationship with Sophora flavescens.